EMOTIONAL INTELLIGENCE, LEARNING MOTIVATION, AND PROCEDURE TEXT WRITING ABILITY: A CORRELATIONAL STUDY AT MTS NEGERI 3 SOUTH BOLAANG MONGONDOW - Nursiti Aisyah Paputungan; Rian Kadir; Marwan B. Suleman (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
This study aimed to examine the relationship between emotional intelligence, motivation to learn English, and students’ ability to write procedural texts among ninth-grade students at MTs Negeri 3 Bolaang Mongondow Selatan. The study employed a quantitative correlational design involving 75 students selected through total sampling. Data were collected using emotional intelligence and learning motivation questionnaires, as well as a procedural text writing test, and were analyzed using correlation and regression techniques. The results indicated a positive and significant relationship between emotional intelligence and students’ learning motivation, with self-motivation showing a strong positive correlation (r = 0.673, p < 0.05). In addition, both emotional intelligence and learning motivation were positively and significantly correlated with students’ procedural text writing ability. Regression analysis further revealed that emotional intelligence and learning motivation jointly contributed significantly to students’ writing performance. These findings suggest that affective factors play an important role in supporting students’ engagement and success in English writing, particularly in procedural text production. Therefore, integrating emotional intelligence development and motivational support into English instruction is essential to enhance students’ writing skills and overall learning outcomes.